Effect of the doping method on luminescent properties of ZnS:Ag - Bacherikov, Yu.Yu.; Zhuk, A.G.; Okhrimenko, O.B.; Pecherskaya-Gromadskaya, E.Yu.; Kidalov, V.V.; Optasyuk, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
The effect of doping the method on the luminescent characteristics of dispersed ZnS doped with Ag has been studied in this work. The analysis of ratio of the intensity of photoluminescence bands related with the centres caused by Ag impurity and the intrinsic defects has led to the conclusion that formation of dispersed ZnS:Ag prepared using the self-propagating high-temperature synthesis (SHS) has several advantages: doping occurs directly in the process of material synthesis, possibility of simultaneous preparation of two fractions with different particle sizes, in ZnS:Ag-SHS with particle sizes greater than 20 nm there is a lower concentration of defects as compared to that in ZnS:Ag obtained using the thermal doping method.